Early life stages of Notothenioidei from the Kerguelen Islands ... - Koubbi, Philippe; Duhamel, Guy; Camus, Patrick (Cybium, 1990)
Morphology, meristics and pigmentation have been used in combination with knowledge of adult reproduction and habitat to identify larvae of Notothenioidei from the Kerguelen Islands. The larvae have been collected regularly with plankton since 1986. Eleven species belonging to this suborder occur in the Indian sector of the Southern Ocean. Most of the descriptions of larvae are original and include seven species of Nototheniidae, two species of Channichthyidae and one of Harpagiferidae. The features observed on the larvae reinforce the distinctions between the genera and subgenera of the Nototheniidae suggested by Andersen (1984). ...